A review of the therapeutic potential of histone deacetylase inhibitors in rhabdomyosarcoma - Selim, Omar; Song, Clara; Kumar, Amy; Phelan, Rebecca; Singh, Arun; Federman, Noah (Frontiers in Oncology, 2023)
Rhabdomyosarcoma (RMS) is a rare and highly aggressive soft tissue sarcoma that primarily affects children. Relapsed/refractory, metastatic, and translocation positive RMS have dismal outcomes, and improvements in survival have been minimal in "high-risk" disease. Recently, histone deacetylase inhibitors (HDACi) have garnered attention for activity in RMS. HDACi are the focus of ongoing clinical trials and new study concepts. As such, we created an impactful and first-in-class review of the preclinical evidence that exists supporting HDACs in the pathogenesis of RMS and the evidence surrounding HDACi in RMS and other soft tissue sarcomas.